Cambridge Learner's Dictionary English-Turkish with CD-ROM (Dictionary Book & CD Rom) - Cambridge University Press (Cambridge Cambridge University Press, 2015)
A new edition of the Cambridge Learner's Dictionary for Turkish speaking learners of English. In this semi-bilingual dictionary, word partner boxes show how words are used together, helping develop natural sounding English. The thesaurus boxes provide alternatives to over-used words, helping widen your vocabulary. Also, Common Mistakes boxes taken from the Cambridge Learner Corpus help avoid typical errors made by Turkish learners of English. The CD-ROM includes the whole dictionary in a handy searchable format and much more, too! You can listen to every word in British and American English - and even record yourself for comparison. The unique SMART thesaurus helps build vocabulary. QUICKfind, a mini pop-up version of the dictionary, lets you look up words as you work with no effort. Hundreds of interactive vocabulary practice exercises help monitor your progress.
There is a CD ROM